A rare case of kinked reinforced endotracheal tube in an intensive care unit: a case report. Issue 1 (January 2020) - Nikandish, Reza; Farbood, Arash; Amini, Afshin; Tarkesh, Firoozeh; Gharache, Shekufeh
Abstract : Abstract: Reinforced endotracheal tubes (ETTs) are regularly applied in anesthetic practices to prevent compression or kinking. Although these tubes are designed to bend easily and prevent obstruction, they still carry a potential hazard of being obstructed following external forces. In this article, we reported an unusual case in which a reinforced ETT was collapsed due to the patient bite. The patient's bite force on the tube resulted in obstruction, hypoxia, and desaturation. To overcome this near-fatally condition, we removed the blocked reinforced ETT. Abstract : Resumen: Los tubos endotraqueales reforzados (TET) se usan generalmente en la práctica anestésica para evitar la compresión o el acodamiento. Aun cuando dichos tubos están diseñados para flexionarse fácilmente y prevenir obstrucciones, de todos modos, existe la posibilidad de que se obstruyan, como consecuencia de fuerzas externas. En el presente trabajo reportamos un caso inusual en el cual se colapsó el TET a causa de la mordida del paciente. La fuerza de mordida sobre el tubo produjo obstrucción, hipoxia y desaturación. Con el fin de superar esta condición casi fatal, retiramos el TET reforzado bloqueado. Abstract : Supplemental Digital Content is available in the text